The Panopticon and the Ponopticism in the Background of Globalization - Barevičiūtė, Jovilė (Problemos, 2004)
The idea of panopticism and the form of panopticism power are modulated against the background of globalization, which is one of the most vivid phenomenon of the postmodernism epoch in this article. The attitude, expressed by Z. Bauman, who is one of the most famous contemporary philosophers, towards the Panopticon and Sinopticon as well as towards panopticism and sinopticism is considered. An architectural model of the structure serves as the condition of possibility of power relationship and evaluation of the disciplinary apparatus. Comparison of the Panopticon with the Sinopticon is carried out. The research of electronic data banks, the dots of contiguity and difference of the Panopticon structures is done. Why the data banks in the cyber-space reach the highest degree of mobility, whereas the Panopticon immobilizes each individual, who finds himself or herself in the territory of the unique prison?
Keywords: power relationship; cyber-space; electronic data banks.